EDUKASI KESEHATAN GIGI DAN MULUT SEJAK DINI BAGI SISWA DI SMA PEMBANGUNAN LABORATORIUM UNP PADANG - Haria Fitri; Nila Kasuma; Rahmi Khairani Aulia; Reno Wiska Wulandari (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Dental and oral health is a part of body health that cannot be separated from one another because it will affect the overall health of the body. Teeth are one part of the body that functions to chew, speak and maintain the shape of the face, so it is important to maintain healthy teeth as early as possible so they can last a long time in the oral cavity. Several epidemiological studies have shown that oral hygiene and gingival status of various degrees of severity are commonly found in children and adolescents. Teenagers often experience health problems, one of which is dental and oral hygiene problems. School students are the right group for health promotion efforts. This educational activity aims to increase knowledge about dental and oral health and to change individual and/or community behavior in the health sector. The method implemented in this educational activity is to use the online method which is carried out with 57 students at the UNP Padang Laboratory Development High School. The results showed an increase in the mean score from the pretest results of 6.13 and the posttest average score of 8.32, so it can be concluded that educational activities through online media can increase the knowledge of SMA Development Laboratory UNP Padang students in maintaining oral health from an early age. Furthermore, counseling activities using this method can be an option for health workers, especially dentists so that they can reach more remote areas.